2013
DOI: 10.3402/tellusb.v65i0.20213
|View full text |Cite
|
Sign up to set email alerts
|

Three-decade changes in chemical composition of precipitation in Guangzhou city, southern China: has precipitation recovered from acidification following sulphur dioxide emission control?

Abstract: We examined if precipitation had recovered from acidification in Guangzhou, the third biggest city in China, and if sulphur deposition in precipitation had decreased, and to what extent if yes, following abatement strategies in sulphur dioxide (SO2) emission and energy use implemented since 2001. SO2 emissions were decreasing steadily since 2001, but a marked recovery of precipitation acidity occurred only since 2005; precipitation pH values decreased from 4.65 in 2001 to 4.34 in 2005 and then increased to 5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Although SO 2 emissions have declined across Europe and eastern North America since the 1990s (Oulehle et al, 2011) and in China since 2005 (Fang et al, 2013), the contribution…”
Section: Introductionmentioning
confidence: 99%
“…Although SO 2 emissions have declined across Europe and eastern North America since the 1990s (Oulehle et al, 2011) and in China since 2005 (Fang et al, 2013), the contribution…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the fraction of NO 3 -wet deposition gradually increased during the analyzed 15-year period over East Asia, indicating that further attention should 30 be paid attention to the deposition of NO 3 -and related Nr species. This has been coincided with previous reports on several cities in China; Nanjing (Tu et al, 2005), Shenzhen (Huang et al, 2008), Guangzhou (Fang et al, 2013), Pearl River Delta region (Lu et al, 2015), and Beijing . Our study reinforced these implications on a whole scale over East Asia.…”
Section: Long-term Trend Of Wet Deposition Amountmentioning
confidence: 48%
“…Analyses for long-term precipitation chemistry are still limited. For example, precipitation chemistry over periods of longer than 10 years has been reported for Guangzhou during 1983(Fang et al, 2013, Shenzhen during 1986-2006(Huang et al, 2008), Lijiang during 1989-2006(Zhang et al, 2012, and Nanjing during 1992-2003 (Tu et al, 2005). This study's long-term, 15-year 20 analysis will provide a comprehensive view of the precipitation chemistry over East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, regional nitrogen emissions and depositions also increased [60][61][62]. This changed the compositions of acid rain [63,64] and brought a new challenge for the regional eco-environment and the regional economies [26,65,66]. (Tables 3-5) and related subsectors transferred from the south to the central and north (Figure 6 and Table 6).…”
Section: Discussionmentioning
confidence: 99%